Application of Response Surface Methodology for Parametric Optimization of Natural Convection in Trapezoidal Cavity containing Hybrid Nanofluid - Md Arifin, Norihan; Mustafa, Mohd. Shafie; Mohd Hashim, Muhamad Hasif; Ab Ghani, Aniza; Mohamad Som, Ahmad Nazri (2024)
This work presents a numerical analysis for exploring heat transfer phenomena in a trapezoidal cavity using natural convection. Because of the numerous real-world applications of nanofluids in engineering development, hybrid nanofluids are used as fluid mediums in the fluid field. The copper (Cu) and alumina (〖Al〗_2 O_3) nanoparticles are suspended in water to make a hybrid nanofluid. A trapezoidal is taken with the left heated wall, and right cold wall and filled with hybrid nanofluid, and the remaining walls of the cavity are kept at adiabatic. The governing equations have been solved by the finite element method (FEM). The graphical computation of the effective parameters is precisely scrutinized on the profiles of velocity, isotherms, and average Nusselt number. As a novelty, the response surface method (RSM) has been applied to achieve the optimum value of the involved parameters. It provided a correlation for the average Nusselt number based on the investigated determinants due to the conflicting influence of the study factors.